Status of wonder women: challenges for young future women entrepreneurs in Pakistan - Khan, Ghazala; Naveed, Rana Tahir; Jantan, Amer Hamzah (Institute of Business Management, 2018)
Women entrepreneurs in Pakistan face numerous difficulties in their successful business career and poses unusual status and intensity. These challenges affect women entrepreneurs differently depending on diverse situations. This study is aimed to shed light on the challenges affecting women to get success in business and to point out the issues faced by them while being entrepreneurs. It highlighted the challenges confronted by Pakistani business women and to open discussion which may empower researchers to get the clear scenario of occupations and industry down to the four-digit code. Gathering primary data from Labor Force Survey,(2014-15), UN Women, (2016), Pakistan Bureau of Statistics.(2015),The little data book on financial inclusion, (2015), Women Economic Participation and Empowerment Status Report, (2016-2015), this study provides recommendations, assisting the federal and provincial agencies to introduce women friendly laws to reduce gender biases as well as to take notes on gender -specific measure to ease the business environment for women in Pakistan.